Intellectual Capital and Innovation Performance: Systematic Literature Review - Mostafa A. Ali; Nazimah Hussin; Hossam Haddad; Reem Al-Araj; Ibtihal A. Abed (Risks, 2021)
Over the years, several studies have been conducted to identify the impact of various intellectual capital components on the organizational performances. However, most of these works greatly replicated the applications and uses of different intellectual capital components (human, structural, relational, social) without addressing the shortcomings related to their empowerment toward the innovation perception of the organizations. Based on this fact, we comprehensively reviewed the existing literatures that strongly influenced the innovation performance of the financial sector. Standard inclusion and exclusion criteria were used for the critical and systematic evaluation of the past studies. It identified the main limitations of intellectual capital components efficiency in the financial sector that could considerably affect their desired innovation performances in the dynamic and competitive market scenarios. In addition, a correlation was established among the organizational growth of intellectual capital components and innovation performance, leading to positive implications on intellectual capital components development.